(untitled) (Jurnal EurekaMatika, 2020)
In this research, land price estimation was conducted using the Universal Kriging method. The Kriging method utilizes spatial values at sampled locations and a variogram to predict values at other unsampled and/or non-sampled locations, where these predicted values depend on their proximity to the sampled locations. The estimation calculation process was carried out with the assistance of R software using the sp and gstat packages. Based on the research results, information was obtained regarding unsampled land prices around the locations where field surveys were conducted; specifically, 186 estimated points were identified. The highest land price was found to be Rp 2,251,604.1 /m² at the location with abscissa X 632,564 meters and ordinate Y 9,764,654 meters, with an error variance of 9.82 x 10^17. Meanwhile, the lowest land price was Rp 500,615.6 /m² at the location with abscissa X 623,854 meters and ordinate Y 9,766,992 meters, with an error variance of 1.20 x 10^18. Keyword: Land price, Universal Kriging method. ABSTRAK Pada penelitian ini dilakukan pengestimasian harga tanah dengan metode Universal Kriging. Metode Kriging memanfaatkan nilai spasial pada lokasi tersampel dan variogram untuk memprediksi nilai pada lokasi lain yang belum dan/atau tidak tersampel dimana nilai prediksi tersebut tergantung pada kedekatannya terhadap lokasi tersampel. Proses penghitungan estimasi dilakukan dengan bantuan software R menggunakan package sp dan gstat. Berdasarkan hasil penelitian, diperoleh informasi harga tanah yang tidak tersampel di sekitar lokasi yang sudah dilakukan survey lapangan yaitu sebanyak 186 titik hasil estimasi dengan harga tanah tertinggi yaitu sebesar Rp 2.251.604,1 /m² pada lokasi absis X 632564 meter dan ordinat Y 9764654 meter dengan variansi error sebesar 9,82E+17 dan nilai harga tanah terendah sebesar Rp 500.615,6 /m² pada lokasi absis X 623854 meter dan ordinat Y 9766992 meter dengan variansi error sebesar 1,20E+18.